Lifestyle Impact on Cognitive Decline and Neurodegeneration Overview - David, Alexander Victor Anand; Parasuraman, Subramani (Free Radicals and Antioxidants)
Cognitive decline is a part of a natural phenomenon that eventually happens to almost every one as they age. It results from a combination of lifestyle habits, genetic factors, trauma or just gradual wearing-out of one’s nervous system. The effects of lifestyle and behavior which include patterns of dietary intake, physical activities as well as practicing unhealthy habits such as smoking and alcohol consumption, have been globally emphasized and embraced time and again as a crucial component to avoid serious health complications. It is also been included as an evidence-based guideline for children, adolescents and adults from diverse populations in all countries. Healthy lifestyle behaviors and therapeutic lifestyle changes were emphasized and reaffirmed as central to cardiovascular health promotion and risk reduction, respectively. Certain healthy behaviors known to combat cancer, cardiovascular disease, diabetes and may also reduce the risk of cognitive decline. Simple lifestyle changes might delay the start of cognitive decline and dementia or slow its progression. Activities that boost your body and brain are such as staying mentally active, engaging in regular physical activity and eating a heart-healthy diet. There are also evidences where people may benefit from staying socially engaged with friends, family and the community. People can reduce the risk of cognitive de cline by making key lifestyle changes. There are measures which can be taken to modify their lifestyle while they still can before it’s too late to stop if not to minimize the onset of neuron degeneration.
Keywords: Alzheimer’s disease; Lifestyle; Neuron degeneration; Cognitive decline; Demen tia; Neurological deficit